Serum amyloid alpha 1-2 are not required for liver inflammation in the 4T1 murine breast cancer model - He, Chenfeng; Konishi, Riyo; Harata, Ayano; Nakamura, Yuki; Mizuno, Rin; Yoda, Mayuko; Toi, Masakazu; Kawaguchi, Kosuke; Kawaoka, Shinpei (Frontiers in Immunology, 2023)
Cancers induce the production of acute phase proteins such as serum amyloid alpha (SAA) in the liver and cause inflammation in various host organs. Despite the well-known coincidence of acute phase response and inflammation, the direct roles of SAA proteins in inflammation in the cancer context remains incompletely characterized, particularly in vivo. Here, we investigate the in vivo significance of SAA proteins in liver inflammation in the 4T1 murine breast cancer model. 4T1 cancers elevate the expression of SAA1 and SAA2, the two major murine acute phase proteins in the liver. The elevation of Saa1-2 correlates with the up-regulation of immune cell-related genes including neutrophil markers. To examine this correlation in detail, we generate mice that lack Saa1-2 and investigate immune-cell phenotypes. RNA-seq experiments reveal that deletion of Saa1-2 does not strongly affect 4T1-induced activation of immune cell-related genes in the liver. Flow cytometry experiments demonstrate the dispensable roles of SAA1-2 in cancer-dependent neutrophil infiltration to the liver. Consistently, 4T1-induced gene expression changes in bone marrow do not require Saa1-2. This study clarifies the negligible contribution of SAA1-2 proteins in liver inflammation in the 4T1 breast cancer model.